THE EFFECT OF LEAF GREEN GRASS JELLY EXTRACT (Cyclea L. barbata Miers) TO MOTILITY IN MICE BALB/C MALE THAT EXPOSED SMOKE - Nurlela, Jihan (Majority, 2015)
Abstract Free radical compounds contained in cigarette smoke gives disruption in membrane abnormalities and motility of spermatozoa. Phenolic compounds contained in leaf of Cyclea barbata L. Miers acts as antioxidants can stop the chain of free radicals in lipid oxidation. Cyclea L. barbata Miers is one of the potential medicinal plants known as green grass jelly. Besides carbohydrates, fats and proteins, Cyclea L. barbata Miers also contain other compounds such as polyphenols, flavonoids that contain antioxidants. Giving leaf of Cyclea L. barbata Miers extract can improve motility of spermatozoa in mice Balb/c males were exposed to cigarette smoke significantly. Keywords: cigarette Smoke, cyclea barbata l. miers, motility of spermatozoa Abstrak Senyawa radikal bebas yang terkandung dalam asap rokok memberikan gangguan pada kelainan membran dan motilitas spermatozoa. Senyawa fenol yang terkandung dalam daun Cyclea barbata L. Miers berfungsi sebagai antioksidan dapat menghentikan rantai radikal bebas pada oksidasi lipid. Cyclea barbata L. Miers merupakan salah satu tanaman obat potensial yang lebih dikenal masyarakat sebagai cincau hijau. Selain karbohidrat, lemak dan protein, Cyclea barbata L. Miers juga mengandung senyawa-senyawa lainnya seperti Polifenol, Flavonoid yang mengandung antioksidan. Pemberian ekstrak daun Cyclea barbata L. Miers dapat memperbaiki motilitas spermatozoa pada Mencit Balb/c jantan yang dipapar asap rokok secara signifikan. Kata kunci: asap rokok, cyclea barbata l. miers, motilitas spermatozoa